Effect of hydroxypropyl distarch phosphate on the physicochemical characteristics and structure of shrimp myofibrillar protein. (April 2022) - Mi, Jie; Zhao, Xinzhi; Huang, Ping; Hong, Jingxia; Jia, Ru; Deng, Shanggui; Yu, Xunxin; Wei, Huamao; Yang, Wenge
Abstract: Effect of hydroxypropyl distarch phosphate (HPDSP) on the physicochemical properties and structure of shrimp ( Penaeus vannamei) myofibrillar protein (MP) were investigated, and the changes in chemical bonds, water state, secondary structure content and protein composition of MP and MP gel (MPG) were analyzed. The results showed that the addition of 1.0% HPDSP could improve breaking force, breaking distance, gel strength and water holding capacity (WHC) of MPG, but the excessive starch could break down the structure of MPG and cause a decrease in gel quality. In addition, HPDSP had no significant effect on the relative content of MPG protein secondary structure which is consistent with the result of protein composition, while heat induction led to a decrease in the content of α-helix and an increase in the content of β-sheet and random coil. The result of the water state demonstrated that HPDSP could shorten the T2 spin-spin relaxation time of MPG and cause the exchange of water from free water to bound water. In terms of microstructure, the MPG containing 1% HPDSP had the densest three-dimensional network structure. Therefore, the overall results suggested that starch-protein interaction had the most beneficial performance of MPG with the addition of 1% HPDSP. Graphical abstract: Image 1 Highlights: The best MPG was obtained with addition of 1% HPDSP. MHC degradation during heating. HPDSP caused exchange of water from free water to bound water. Disulfide and hydrophobic bonds of MP formatted during heating. Excessive HPDSP led to the microstructure of MPG broken.